1986
DOI: 10.1002/food.19860300382
|View full text |Cite
|
Sign up to set email alerts
|

The influence of early postnatal overnutrition on postprandial energy expenditure in rats

Abstract: Short communication) L. AUST, R. NOACK and J. PROLLOvernutrition in rodents during early postnatal life induced by breeding in small nest sizes leads to distinct metabolic changes, which remain throughout life even under conditions of free access to normal food. An accelerated body fat accumulation and a probably higher efficiency of energy utilization render this animal model suitable for the study of relations between the development of an obese state and its metabolic causes [ 1, 21. There is increasing evi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
2
0

Year Published

1987
1987
2002
2002

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 4 publications
1
2
0
Order By: Relevance
“…There are only very scarce results in the literature about EE in SL animals in comparison with NL animals. It has been reported that SL rats show a reduced postprandial EE at 7 -9 weeks of life (Aust et al 1986). In the present study, we found that total daily EE was virtually the same for SL and NL rats at week 8 and 12.…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…There are only very scarce results in the literature about EE in SL animals in comparison with NL animals. It has been reported that SL rats show a reduced postprandial EE at 7 -9 weeks of life (Aust et al 1986). In the present study, we found that total daily EE was virtually the same for SL and NL rats at week 8 and 12.…”
Section: Discussionsupporting
confidence: 73%
“…*P,0•05. 1972; Parizková & Petrásek, 1979;Aust et al 1985). However, energy balance was not determined in these studies and our present results show that even by 5 weeks of age there was no difference in energy retention between the groups.…”
Section: Discussionmentioning
confidence: 48%
See 1 more Smart Citation